Gene editing the phytoene desaturase alleles of Cavendish banana using CRISPR/Cas9 - Eftekhari, Fatima; Dugdale, B.; Kleidon, J.; Brinin, A.; Shand, K.; Waterhouse, P.; Dale, J. (SPRINGER, 2018)
Bananas are a staple food source and a major export commodity worldwide. The Cavendish dessert banana is a triploid AAA genome type and accounts for around 47% of global production. Being essentially sterile, genetic modification is perhaps the only pathway available to improve this cultivar. In this study, we used the CRISPR/Cas9 gene editing system to deliver a self-cleaving polycistronic guide RNA (gRNA) designed to target exon 1 of the Phytoene desaturase (PDS) gene in the Cavendish cultivar “Williams”. Genotyping of 19 independent events showed a 100% PDS modification rate primarily in the form of insertions (1–105 nt) or deletions (1–55 nt) (indels) at the predicted cleavage site. Tri-allelic disruptive modifications were observed in 63% of plants and resulted in both albinism and dwarfing. Pale green (16%) and wildtype green (21%) phenotypes generally correlated with in-frame indels in at least one of the three PDS alleles. Editing efficiency was dependent on both target site selection and Cas9 abundance. This is the first report of a highly effective CRISPR/Cas9 modification system using a polycistronic gRNA in Cavendish banana. Such an editing platform will be of considerable utility for the development of disease resistance and novel agro-traits in this commercially important cultivar into the future.